A 3D multidirectional piezoelectric energy harvester using rope-driven mechanism for low frequency and ultralow intensity vibration environment. (20th December 2021) - Zhang, Jinhui; Lin, Maoyu; Zhou, Wei; Tang, Lihua; Qin, Lifeng
Abstract: Though numerous piezoelectric vibration energy harvesters (PVEHs) have been designed and investigated to provide power supply for wireless sensors or wearable devices, it remains a challenge for traditional PVEHs to work effectively in an environment of low frequency, low acceleration and multidirectional vibrations. This work presents a PVEH using a low-frequency energy-capturing resonant system formed by a rolling ball in a hemispherical shell and driven by a rope. Due to the symmetry of the sphere, the ball can be excited at multiple directions in 3D space, and the piezoelectric beam can be pulled by the ball through a rope in multiple directions. Thus, the efficient multidirectional energy harvesting under low frequency (<10 Hz) and ultralow intensity (<0.1 g ) vibrations could be realized. A mass-spring-damper equivalent model was built to understand the operation mechanism of the proposed PVEH. The results show that the proposed PVEH has a potential to collect energy in any direction in 3D space, and could achieve a good angle bandwidth with 360° for ϕ and 240° for β under the excitation of a = 0.04 g, f = 6.8 Hz with the acceleration a ⃗ a, β, φ defined in the spherical coordinate system. The developed PVEH can generate 6.5 μ W under a low-intensity excitation (0.03 g ), and the normalized power density can reach 22.63 μ W/(cm 3 g 2 Hz). Moreover, the minimum start-up acceleration analysis of the proposed PVEH indicates that the PVEH can capture multidirectional energy from vibrations as low as 0.01 g . In addition, both simulation and experimental study on rope redundancy and ball mass show that they can be used to adjust the device performance easily without structure re-fabrication. Overall, this study demonstrates a new mechanism that could effectively harvest low frequency, ultralow intensity and multidirectional vibration energy.